The philosophy of information - Floridi, Luciano, 1964- (Oxford : Oxford University Press, 2011)
Luciano Floridi presents a book that will set the agenda for the philosophy of information - the study of the nature of information and the development of information-theoretic and computational methodologies for philosophy.
Description based on online resource; title from PDF title page (viewed on May 12, 2011).
Includes bibliographical references and index.
Keywords: Information science -- Philosophy